Responsible Malaysia Madani In Aidilfitri Discovery for Autism Children - Hadijah, Ahmad (2023)
The number of children with disabilities is increasing every year. This trend is expected to continue, with even more children expected to be diagnosed in the coming years. According to the Department of Social Welfare, there are 152,065 registrations for persons with disabilities (OKU) status as of January 2023.